Little Dorrit - Dickens, Charles, 1812-1870. (New York : Distributed by Random House, 1992)
The story of a family and the system of debtors' prisons as symbols of the social and psychological imprisonment of 19th century England.
Includes bibliographical references.
Wilson's Fiction.
Adult
Keywords: Marshalsea Prison (Southwark, London, England) -- Fiction; Debt, Imprisonment for -- Fiction; Debt -- Fiction; London (England) -- Social conditions -- Fiction; London (England) -- Social life and customs -- 19th century -- Fiction; London (England) -- Fiction; Didactic fiction